(untitled) (Academia Journal of Medicine, 2026)
Aim: This study aimed to evaluate and compare the microleakage of Type II glass ionomer cement (GIC), Type IX GIC, and resin-modified glass ionomer cement (RMGIC) restorations in primary teeth. Materials and Methods: Thirty over-retained, non-carious primary molars beyond their exfoliation period were collected and randomly divided into three groups (n = 10 each). Group A: Type II GIC; Group B: Type IX GIC; Group C: RMGIC. Standardized Class V cavities were prepared on the buccal surface of each tooth without mechanical retention and restored with the respective materials. All samples were subjected to thermocycling for 250 cycles at varying temperatures, followed by coating with nail varnish. The specimens were then immersed in 0.5% methylene blue dye for 24 hours. Teeth were sectioned buccolingually through the center of the restoration and evaluated under a stereomicroscope for dye penetration. The data obtained were analyzed using Kruskal–Wallis ANOVA and Mann– Whitney U test. Results: The RMGIC group demonstrated comparatively higher microleakage than the other groups. However, no statistically significant difference was observed among the three groups (P > 0.05). Conclusion: Within the limitations of this study, Type II GIC, Type IX GIC, and RMGIC showed comparable microleakage performance in primary teeth.